(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The market of herbal and natural shampoo in Karnataka functions within the setting of a rapidly expanding number of eco-labels that make consumers more sensitive to the genuineness of environmental advertising. This paper looks at the perceived greenwashing on brand trust and purchase intention by consumers of herbal shampoo in Karnataka through brand trust. There is a tested moderated mediation model where Environmental Knowledge (EK) is the moderator of the relationship between Perceived Greenwashing (PGW) and Brand Trust (BT), with Brand Trust (BT) being a mediator between Purchase Intention (PI) and Perceived Greenwashing (PGW). A five-point Likert scale structured questionnaire was used to collect the data of 400 respondents and was analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with bootstrapping of 5,000-subsamples by using SmartPLS 4. All four constructs demonstrated satisfactory reliability and validity (Cronbach’s α: 0.732–0.799; CR: 0.832–0.868; AVE: 0.555–0.621). Brand Trust had a significant negative effect (β = -0.43, p < 0.001) on Perceived greenwashing, leading to purchase intention (β = +0.43, p < 0.001). Partial mediation was established: the moderating role of brand trust on purchase intention through perceived greenwashing was also significant (β = -0.177, p < 0.001) but there was also direct relationship (β = -0.221, p < 0.001).). Environmental Knowledge significantly amplified the negative effect of greenwashing on trust through the interaction term (β = 0.258, p < 0.001). The model accounted 28.9% variation in brand trust, and accounted 29.9% in purchase intention. These results can be applied to herbal FMCG brands and organizations that regulate in the booming green Indian consumer market.